Photochemical Oxidation of Phenol in Olefins Plant Effluent by UV/H2O2 and Photo-Fenton Processes (Case Study) - Torabian, A.; Jamshidi, N.; Azimi, A.A.; Nabi Bidhendi, G.R.; Jafarzadeh, M.T. (Asian Journal of Chemistry, 2010)
In this study, the application of advanced photochemiocal oxidation technologies (UV/H2O2, UV/H2O2/Fe(II) and UV/H2O2/Fe(III)) were investigated in lab-scale experiments for degradation of phenol in olefin plant effluent of Tabriz petrochemical company. The study shows that the Photo-Fenton process, (a mixture of hydrogen peroxide and ferrous or ferric ion), was the most effective treatment process under acidic conditions and produced a higher rate of degradation of phenol at a very short radiation time. It accelerates the oxidation rate by 5-7 times the rate of the UV/ H2O2 process. The reaction was influenced by pHvalue, the input concen-tration of H2O2 and the amount of the iron catalyst and the type of iron salt. Complete phenol removal was obtained by all applied processes. The experimental results show that the optimum conditions were obtained at a pH value of 3, with molar ratio [H2O2]/[phenol] equal 14.4 and molar ratio [iron]/[H2O2] is 0.057 and 0.043 for UV/ H2O2/Fe(II) and UV/H2O2/Fe(III), respectively. As for the UV processes, UV/ H2O2/Fe(III) showed the highest degradation rate.